The Influence of Product Development and Promotion on Purchase Intention Moderated by Social Media Influencers - Resdiansyah Resdiansyah; Ratlan Pardede (Riviera Publishing, 2024)
This study aimed to analyze the effect of product development and Promotion on purchase intention, with the role of social media influencers as moderating variables. This research focuses on consumers of TEKIRO brand hand tools products distributed by PT Altama Surya Anugerah (ASA) - Indonesia. The research method used is quantitative, with a Google Forms survey approach. The research sample consisted of 190 respondents who were consumers of TEKIRO hand tools products in 15 major cities in Indonesia. The sampling technique used is non-probability sampling with the quota method. This data was collected by online and offline questionnaires, which the researchers then analyzed using Structural Equation Modeling (SEM) with the AMOS version 23 application. The study results indicate that product development has a significant positive effect on purchase intention. The Promotion has no significant effect on purchase intention. Social media influencers strengthen the positive Influence of product development on purchase intention. However, social media influencers do not strengthen the Influence of Promotion on purchase intention. This research implies that companies must prioritize innovative and sustainable product development and can utilize social media influencers who are credible, relevant to the company's business, know the influencer's audience, and have a good reputation to increase consumer purchase intention.